2005
DOI: 10.1210/en.2005-0254
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Gene Is Expressed in Multiple Tissues in the Chicken: Food Deprivation Influences Adiponectin Messenger Ribonucleic Acid Expression

Abstract: Adiponectin is a cytokine hormone originally found to be secreted exclusively by white adipose tissue. However, recent evidences suggest that adiponectin is also produced in brown adipose tissue and skeletal muscle. The present study investigated the expression of adiponectin mRNA in various tissues in the chicken. We also studied the effect of food deprivation on adiponectin gene expression in adipose tissue, liver, anterior pituitary gland, and diencephalon in the chicken. The open reading frame of chicken a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 45 publications
7
103
1
2
Order By: Relevance
“…Adiponectin has already been found in the ovaries of different species, including chicken (Maddineni et al 2005) and porcine (Lord et al 2005, Ledoux et al 2006. …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Adiponectin has already been found in the ovaries of different species, including chicken (Maddineni et al 2005) and porcine (Lord et al 2005, Ledoux et al 2006. …”
Section: Discussionmentioning
confidence: 97%
“…Placental adiponectin mRNA expression is increased during pregnancy in rat, whereas AdipoR2 has the contrary pattern (Caminos et al 2005). Adiponectin, AdipoR1 and AdipoR2 are also present in porcine (Lord et al 2005, Ledoux et al 2006) and chicken ovaries (Maddineni et al 2005, Ramachandran et al 2006. In this latter species, results from our laboratory have shown that adiponectin mRNA expression is 30-fold higher in theca than in granulosa cells (Chabrolle et al in press).…”
Section: Introductionmentioning
confidence: 84%
“…The role of leptin in birds has been hotly debated in the past (71)(72)(73)(74), and the presence of this hormone in the avian circulation has not been convincingly demonstrated (71,(75)(76)(77). Adiponectin, orexin, and obestatin have been studied only at the level of gene cloning or gene expression, but few functional data are available (78)(79)(80)(81)(82). Thus, the present study represents a break-through with regard to the role of appetite-stimulating or -suppressing hormones as physiological modulators of stopover decisions during migration.…”
Section: Discussionmentioning
confidence: 99%
“…We identified the expression of full-length mRNAs encoding chicken adiponectin, ADIPOR1 and ADIPOR2 by RT-PCR analysis and localized adiponectin-, ADI-POR1-, and ADIPOR2-ir cells in the chicken testis. Once thought to be primarily secreted by white adipose tissue, adiponectin has recently been found to be expressed in multiple tissues in the chicken (Maddineni et al 2005). In particular, adiponectin gene expression has been identified in chicken ovarian follicles (Chabrolle et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although adiponectin was once thought to be exclusively secreted from adipose tissue, we have recently detected expression of adiponectin and its receptors in multiple tissues in the chicken (Maddineni et al 2005, Ramachandran et al 2007. However, it is not known whether adiponectin or its receptors are expressed in the chicken testis.…”
Section: Introductionmentioning
confidence: 97%